Epithelial-mesenchymal transition-associated microRNA/mRNA signature is linked to metastasis and prognosis in clear-cell renal cell carcinoma - Mlcochova, Hana; Machackova, Tana; Rabien, Anja; Radova, Lenka; Fabian, Pavel; Iliev, Robert; Slaba, Katerina; Poprach, Alexandr; Kilic, Ergin; Stanik, Michal; Redova-Lojova, Martina; Svoboda, Marek; et al. (Scientific reports, 2016)
Clear-cell renal cell carcinomas (ccRCCs) are genetically heterogeneous tumors presenting diverse clinical courses. Epithelial-mesenchymal transition (EMT) is a crucial process involved in initiation of metastatic cascade. The aim of our study was to identify an integrated miRNA/mRNA signature associated with metastasis and prognosis in ccRCC through targeted approach based on analysis of miRNAs/mRNAs associated with EMT. A cohort of 230 ccRCC was included in our study and further divided into discovery, training and validation cohorts. EMT markers were evaluated in ccRCC tumor samples, which were grouped accordingly to EMT status. By use of large-scale miRNA/mRNA expression profiling, we identified miRNA/mRNA with significantly different expression in EMT-positive tumors and selected 41 miRNAs/mRNAs for training phase of the study to evaluate their diagnostic and prognostic potential. Fifteen miRNAs/mRNAs were analyzed in the validation phase, where all evaluated miRNA/mRNA candidates were confirmed to be significantly deregulated in tumor tissue. Some of them significantly differed in metastatic tumors, correlated with clinical stage, with Fuhrman grade and with overall survival. Further, we established an EMT-based stage-independent prognostic scoring system enabling identification of ccRCC patients at high-risk of cancer-related death. Finally, we confirmed involvement of miR-429 in EMT regulation in RCC cells in vitro.
Keywords: Gene Expression Regulation, Neoplastic; analýza přežití; nádory ledvin; RNA, Messenger; Neoplasm Metastasis; Male; MicroRNAs; karcinom z renálních buněk; Epithelial-Mesenchymal Transition; prognóza; mikro RNA; regulace genové exprese u nádorů; Adult; Kidney Neoplasms; Aged; dospělí; mužské pohlaví; senioři; lidé středního věku; stanovení celkové genové exprese; Survival Analysis; Gene Expression Profiling; senioři nad 80 let; lidé; ženské pohlaví; Humans; Aged, 80 and over; Prognosis; Carcinoma, Renal Cell; Female; metastázy nádorů; messenger RNA; epitelo-mezenchymální tranzice; Middle Aged